Multistep Transformations of DNA Origami Domino Array via Mechanical Forces. Issue 2 (29th November 2022) - Liu, Yan; Ge, Huan; Wang, Yuqi; Tang, Linlin; Pei, Yufeng; Fan, Sisi; Song, Yongxiu; Zhang, Chuan; Song, Jie
Abstract : Nanostructures that display controllable motions and functions are indispensable to build molecular nanomachines. Structural DNA nanotechnology, enabling precise design of complex static and dynamic structures, can be used to construct molecular nanomachines. However, designing complex dynamic structures that present multiple motion behaviors with different stimuli‐responsiveness is full of challenges. Herein, multistep transformations of DNA origami domino array (DODA) triggered by mechanical forces are developed. The DODA consists of small, modular DNA units, which can be regulated by the external forces. Under the expanding and contraction forces exerted by the DNA trigger and G‐quadruplex (G4)‐functionalized loop strand, the units are reconfigured, leading to the programmable transformations of DODA among three conformations. This multistep transformation strategy is applied to construct chiral plasmonic metamolecules, and analyze K + via fluorescence resonance energy transfer (FRET) analysis. Moreover, the strategy shows a diversified approach to build the DNA‐based nanodevices, and may find potential applications in various fields. Abstract : The multistep transformations of DNA origami domino array via mechanical forces exerted by multiple external stimuli are achieved. The strategy can be applied to build visually informational patterns, and construct chiral plasmonic metamolecules, holding the potentials in various fields like biosensing and diagnosis.